A Simple Proof of a Folklore Theorem about Delimited Control - Biernacki, Dariusz; Danvy, Olivier (BRICS Report Series, 2005)
We formalize and prove the folklore theorem that the static delimited-control operators shift and reset can be simulated in terms of the dynamic delimited-control operators control and prompt. The proof is based on a small-step operational semantics that takes the form of an abstract machine.